Surface Interaction of Ionic Liquids: Stabilization of Polyethylene Terephthalate-Degrading Enzymes in Solution - Zara, Zeenat; Mishra, Deepti; Pandey, Saurabh Kumar; Csefalvay, Eva; Fadaei, Fatemeh; Minofar, Babak; Řeha, David (Molecules, 2021)
The effect of aqueous solutions of selected ionic liquids solutions on Ideonella sakaiensis PETase with bis(2-hydroxyethyl) terephthalate (BHET) substrate were studied by means of molecular dynamics simulations in order to identify the possible effect of ionic liquids on the structure and dynamics of enzymatic Polyethylene terephthalate (PET) hydrolysis. The use of specific ionic liquids can potentially enhance the enzymatic hydrolyses of PET where these ionic liquids are known to partially dissolve PET. The aqueous solution of cholinium phosphate were found to have the smallest effect of the structure of PETase, and its interaction with (BHET) as substrate was comparable to that with the pure water. Thus, the cholinium phosphate was identified as possible candidate as ionic liquid co-solvent to study the enzymatic hydrolyses of PET.
Keywords: Hydrolysis; vodíková vazba; Polyethylene Terephthalates; hydrolýza; Hydrophobic and Hydrophilic Interactions; Phthalic Acids; Protein Conformation; Solvents; rozpouštědla; hydrolasy; simulace molekulární dynamiky; polyethylentereftaláty; iontové kapaliny; Molecular Dynamics Simulation; Hydrolases; Hydrogen Bonding; Burkholderiales; kyseliny ftalové; Ionic Liquids; hydrofobní a hydrofilní interakce; konformace proteinů